2009
DOI: 10.1260/174795409790291402
|View full text |Cite
|
Sign up to set email alerts
|

Tackling Technique, Injury Risk, and Playing Performance in High-Performance Collision Sport Athletes

Abstract: This study investigated the tackling technique of high-performance, collision-sport athletes and documented the relationships between tackling technique and playing experience, playing level, game-specific tackling performance, and injury in these athletes. Twenty-two national rugby league (NRL) and 17 state-based rugby league (SRL) players underwent a standardized one-on-one tackling drill in a 10 m grid. Video footage was taken from the rear, side, and front of the defending player. Tackling technique was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
109
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(121 citation statements)
references
References 17 publications
9
109
3
Order By: Relevance
“…Playing experience has previously been shown to be a significant predictor of playing performance and success in senior rugby league players (Gabbett & Ryan, 2009), and suggested to be a critical variable determining selection into sub-elite first-grade rugby league teams (Gabbett, 2002a;2009;Gabbett, Kelly et al, 2007). It has also been shown that players with 150 matches or greater National Rugby League experience had superior tackling technique to players with less than 150 matches National Rugby League experience (Gabbett & Ryan, 2009), providing further support that sporting expertise develops, at least in part, as a result of accumulated playing experience.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Playing experience has previously been shown to be a significant predictor of playing performance and success in senior rugby league players (Gabbett & Ryan, 2009), and suggested to be a critical variable determining selection into sub-elite first-grade rugby league teams (Gabbett, 2002a;2009;Gabbett, Kelly et al, 2007). It has also been shown that players with 150 matches or greater National Rugby League experience had superior tackling technique to players with less than 150 matches National Rugby League experience (Gabbett & Ryan, 2009), providing further support that sporting expertise develops, at least in part, as a result of accumulated playing experience.…”
Section: Discussionmentioning
confidence: 99%
“…Gabbett, Kelly, and Pezet (2007) investigated the fitness and skill levels of 86 sub-elite (amateur) rugby league players and demonstrated that skill, but not physical qualities, discriminated successful (i.e., subelite first grade) from less successful (i.e., sub-elite second and third grade) players. In a subsequent study, significant differences were reported between professional and semi-professional (Gabbett & Ryan, 2009) and high-skilled and lesser-skilled junior (Gabbett, Jenkins, & Abernethy, 2010) rugby league players on a standardised assessment of tackling proficiency. It was also shown that a dual-task assessment of draw and pass ability (i.e., performance of the skill coupled with a secondary tone recognition task) discriminated higher and lesser-skilled junior rugby league players, when performance of the draw and pass assessment in isolation did not (Gabbett, Wake, & Abernethy, 2011).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Success in rugby league is dependent, at least in part, on tackling ability, the capacity to tolerate physical collisions, and the ability to ÔwinÕ the tackle contest (8,19). Despite the fundamental importance of tackling in rugby league, very little is known about the tackle contest (8,19).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fundamental importance of tackling in rugby league, very little is known about the tackle contest (8,19). Furthermore, there are limited published data on the physical (i.e., physiological and anthropometric) factors that contribute to, or limit, tackling ability in rugby league players (20).…”
Section: Introductionmentioning
confidence: 99%